Muslim educational reforms in nineteenth century India : an analysis of Shibli Nu'mani's thought & practice - Parveen, Nusba (International Institute of Islamic Thought and Civilization (ISTAC), 2005)
The nineteenth century witnessed many efforts by Muslim philosophers and scholars to redefine and readjust to the growing challenges of Western civilization. Education was viewed as the key area of refonn in this process. Traditionally, Muslims had derived their inspiration from the teachings of the Qur'an and Sunnah - acquiring knowledge was viewed not only as an act of worship. but also a means of understanding God's creation and God Himself. However, European material progress and the need for Muslims to catch up with the times led some Muslim scholars and community leaders to adopt European methodology. But this would not be possible without developing a clear relationship with traditional Muslim education. It is in this context that Shibli Nu'mani (1857-1914) becomes so important in modem Islamic thought. Shibli was a philosopher. historian. theologian. poet and an educationist. He was the main person behind the foundation of Nadwatul 'Ulama' Lucknow, through a new curriculum to develop a working relationship between Islamic and Western civilization. In a way his was an effort of Islamization of knowledge in the context of nineteenth century India but it has not yet been studied systematically. This dissertation explains this context and examines his effort. This thesis begins with Shibli 's life and writings and a background of Muslims in the Indian sub-continent with special reference to their educational condition. It studies in detail the British educational policies and their impact on Muslims. This resulted in the efforts of founding traditional Muslim maddris as well as the institutions of modern learning. Then in the third, fourth and fifth chapters it studies the philosophy. contents and method of education as Shibli viewed them. The sixth chapter assesses the contributions or Shibli in educational field with reference to Nadwatul 'Ulama'. Finally, we examine Shibli' s achievements and the causes of his failures. What makes Shibli an important scholar of the nineteenth century is the fact that he propagated a theory different from his contemporaries to improve the education of Muslims. In contrast, most of his contemporaries attempted to teach traditional education to make Muslims retain their religious identity in the changed political situation. Others stressed the teaching of modem science and learning to equip Muslims to face the challenges of modernity. Shibli was the only person who knew the benefits and weaknesses of both systems of education and wanted Muslims to learn the best of both and attempted to bridge the gap between the two. Shibli knew that traditional !slamic education aimed at the attainment of virtues in an individual while pursuing knowledge as an obligatory commandment from God. It was, therefore, hoped that this education would produced scientists and philosophers who were well versed in the Qur'an and hadith. But in his time the promoters of traditional education were ignorant of the demands of the times whereas the modernist group believed that the traditional education was unnecessary. Shihli, therefore, applied a unique method as he used history and kalam to teach Muslims the characteristics of Islamic education. This was the main reason for Muslim stagnation. Shibli believed, because each group was against the other, and it was badly affecting the progress of Muslims. Shibli stressed that both groups need to make the Qur'an their main guide and must give due importance to each subject, while stressing a bigger role of the 'ulama' than they had.